Pengaruh Rasio Profitabilitas terhadap Pertumbuhan Laba yang Dimoderasi oleh Ukuran Perusahaan Perbankan yang Terdaftar di BEI tahun 2019-2023 - Wiyani; Giovanny Bangun Kristianto; Esti Saraswati (Pusat Riset dan Inovasi Nasional, 2025)
As the industrial sector in Indonesia experiences rapid growth, significant changes are required in various sectors, including the economy, to drive progress. Every company strives to achieve maximum profit, with profit growth as the primary performance indicator, including in the banking sector. However, from 2019 to 2023, Indonesia's banking sector faced significant challenges due to the presidential transition and the impact of the COVID-19 pandemic. This crisis led to decreased public trust and lower demand for financing, as well as increased risks of non-performing loans (NPLs). Profit growth refers to the increase in a company's net income over a certain period and is a reflection of effective resource management. This study aims to examine the impact of profitability ratios such as Return on Assets (ROA), Return on Equity (ROE), Gross Profit Margin (GPM), and Net Profit Margin (NPM) on profit growth, as well as analyze the role of company size as a moderating variable. The sample used in this study consists of 30 banking companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, with secondary data collected from the official websites of IDX and the respective companies. Analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) with the help of SPSS software. The results showed that ROA and NPM had a significant positive effect on profit growth, while ROE and GPM had a negative effect on profit growth. Simultaneously, profitability ratios were found to have a significant impact on profit growth. Company size was able to moderate the effect of ROA and ROE on profit growth, but not for GPM and NPM. The coefficient of determination (R²) of 0.409 indicates that 40.9% of the variation in profit growth can be explained by profitability ratios, while the remaining 59.1% is influenced by other variables not included in the model.